Predicting the response to Ondansetron, a 5HT3 receptor antagonist, in irritable bowel syndrome with diarrhoea: the utility of clinical features and objective biomarkers - Garsed, Klara C. (2014)
Background: Patients with diarrhoea predominant irritable bowel syndrome (IBS-D) suffer from loose frequent stools with associated urgency and fear of incontinence. Relief from these symptoms is an important unmet need. The 5-HT3 receptor antagonist Alosetron has been shown to increase stool consistency, decrease urgency and reduce abdominal pain leading to a global increase in satisfaction with treatment [1]. Its use is restricted following an increased incidence of ischaemic colitis and this agent is not available in Europe.